Peer Teaching for Santri: Case Study at Hasbullah Sa’id, Mamba’ul Ma’arif Denanyar Jombang - Al-Farabi, Rifqi Falah; Ibad, Irsyadul; Rizqi, Muhammad Galuh; Mufidah, Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3121, 2024)
This study describes the santri teaching program for Arabic language learning, how the santri teaching learning process, program evaluation, and the supporting and inhibiting factors of the program. This type of research is a descriptive qualitative research type of case study. The subjects of this research are students of the Hasbullah Sa'id dormitory totaling 72 students consisting of students in grades XI, XI, and XII. Data collection techniques used observation of the santri teaching program process, interviews with tutors, audiences, and dormitory coaches. In addition, the documentation of materials and class division. Data analysis used the Miles and Huberman model. The results of this research are (1) The santri teaching learning process is carried out once a month on Sunday nights from 19.30 - 21.00 in the Bisri Syansuri building. XII grade students are selected alternately to serve as tutors, and the others become the audience, (2) The evaluation should be done once every 2 months, and (3) The supporting factors of this program are the enthusiasm of the students in deepening the linguistic sciences, discipline, high motivation, a relaxed and conducive classroom atmosphere so that students are comfortable in participating in the santri teaching program, and adequate facilities that have been prepared. The inhibiting factor of this program is the lack of readiness of student tutors when teaching.